Association between oral fluoroquinolone use and the development of retinal detachment: a systematic review and meta-analysis of observational studies. (18th December 2014) - Chui, Celine S. L.; Wong, Ian C. K.; Wong, Lisa Y. L.; Chan, Esther W.
Abstract: Objectives: Several observational studies have been published investigating the association between oral fluoroquinolone use and the development of retinal detachment; however, the findings are not concordant. This study is a meta-analysis of the existing literature and estimates the overall absolute risk of such an event. Methods: Electronic databases were searched for observational studies on the association between oral fluoroquinolone and retinal detachment up to August 2014. Studies that did not meet the criteria for meta-analysis were narratively reviewed. Cases of retinal detachment during current fluoroquinolone use were also extracted for absolute risk calculation. Results: Seven observational studies were included. Three (case–control and self-controlled case series studies) were eligible for meta-analysis and four (cohort studies) were narratively reviewed. The rate ratio of the case–control studies was 1.82 (95% CI 0.67–4.93), I 2  = 96% and the incidence rate ratio of the self-controlled case series was 1.03 (95% CI 0.84–1.27), I 2  = 36%. Three of the four cohort studies found no significant association between oral fluoroquinolone use and the development of retinal detachment. The pooled absolute risk of retinal detachment whilst on current oral fluoroquinolone treatment is estimated to be 4.85 per 1 000 000 prescriptions (95% CI 0.78–8.91). Conclusions: The findings of this systematic review and meta-analysis do not support an association between oral fluoroquinolone use and the development of retinal detachment. Given the low absolute risk, such an event would be rare if there were an association. The current prescribing practice for fluoroquinolones should not be altered because of a previously suggested potential risk of retinal detachment.